Is There a Proper Type of Management for Branch-Duct Intraductal Papillary Mucinous Tumors of the Pancreas? - Casadei, Riccardo; Ricci, Claudio; Minni, Francesco (JOP. Journal of the Pancreas, 2013)
No abstract available. Image: Allegory (from the Department of Medical and Surgical Sciences - DIMEC. Alma Mater Studiorum - University of Bologna, Italy)